A hybrid method for bubble geometry reconstruction in two-phase microchannels - Wang, Evelyn N.; Devasenathipathy, Shankar; Lin, Hao; Hidrovo, Carlos H.; Santiago, Juan G.; Goodson, Kenneth E.; Kenny, Thomas W. (Experiments in fluids, 2006)
Understanding bubble dynamics is critical to the design and optimization of two-phase microchannel heat sinks. This paper presents a hybrid experimental and computational methodology that reconstructs the three-dimensional bubble geometry, as well as provides other critical information associated with nucleating bubbles in microchannels. Rectangular cross-section silicon microchannels with hydraulic diameters less than 200 mu m were fabricated with integrated heaters for the flow experiments, and the working liquid used was water. Bubbles formed via heterogeneous nucleation and were observed to grow from the silicon side walls of the channels. Two-dimensional images and two-component liquid velocity field measurements during bubble growth were obtained using micron-resolution particle image velocimetry (PIV). These measurements were combined with iterative three-dimensional numerical simulations using finite element software, FEMLAB. The three-dimensional shape and location of the bubble were quantified by identifying the geometry that provided the best match between the computed flow field and the PIV data. The reconstructed flow field through this process reproduced the experimental data within an error of 10-20%. Other important information such as contact angles and bubble growth rates can also be estimated from this methodology. This work is an important step toward understanding the physical mechanisms behind bubble growth and departure.